Distributed Ledger Technology for Smart Cities, the Sharing Economy, and Social Compliance - Pietro Ferraro; C. King; Robert Shorten (IEEE Access, 2018)
This paper describes how distributed ledger technologies (DLTs) can be used to enforce social contracts and to orchestrate the behavior of agents trying to access a shared resource. The first part of this paper analyzes the advantages and disadvantages of using DLTs architectures to implement certain control systems in an Internet of Things (IoT) setting and then focuses on a specific type of DLT based on a directed acyclic graph. In this setting, we propose a set of delay differential equations to describe the dynamical behavior of the Tangle, an IoT-inspired directed acyclic graph designed for the cryptocurrency IOTA. The second part proposes an application of DLTs as a mechanism for dynamic deposit pricing, wherein the deposit of digital currency is used to orchestrate access to a network of shared resources. The pricing signal is used as a mechanism to enforce the desired level of compliance according to a predetermined set of rules. After presenting an illustrative example, we analyze the control system and provide sufficient conditions for the stability of the network.